The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d3ya00102d
|View full text |Cite
|
Sign up to set email alerts
|

Energy storage mechanism, advancement, challenges, and perspectives on vivid manganese redox couples

Abstract: Recently, aqueous based redox flow batteries with manganese (Mn2+/Mn3+) redox couple have gained a significant attention with their eco-friendly, cost-effective, non-toxic, and abundance, making an efficient energy storage solution for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…Before reviewing the MnO 2 /Mn 2+ -chemistry-inspired energy storage devices in detail, the mechanistical or historical aspects of MOR/MRR must be understood (Soundharrajan et al, 2022a). Although several reports regarding modern-day battery devices inspired by MnO 2 /Mn 2+ chemistry have been published recently (Moon et al, 2021;Zheng et al, 2021;Liu et al, 2022a;Yang et al, 2022;Naresh et al, 2023;Ye et al, 2023), the observation of unique MnO 2 /Mn 2+ chemistry was first reported in 1998 in relation to the Zn/ZnSO 4 /MnO 2 rechargeable cell by Kim et al (Kim and Oh, 1998). Although the Zn/ZnSO 4 /MnO 2 rechargeable cell was not coined as ZIBs by Kim et al (Kim and Oh, 1998), the use of mildaqueous ZnSO 4 electrolyte for Zn/MnO 2 rechargeable cells could termed as ZIBs, as per the recent nomenclature.…”
Section: Overview Of the Evolutions Of Aqueous Rechargeable Batteriesmentioning
confidence: 99%
“…Before reviewing the MnO 2 /Mn 2+ -chemistry-inspired energy storage devices in detail, the mechanistical or historical aspects of MOR/MRR must be understood (Soundharrajan et al, 2022a). Although several reports regarding modern-day battery devices inspired by MnO 2 /Mn 2+ chemistry have been published recently (Moon et al, 2021;Zheng et al, 2021;Liu et al, 2022a;Yang et al, 2022;Naresh et al, 2023;Ye et al, 2023), the observation of unique MnO 2 /Mn 2+ chemistry was first reported in 1998 in relation to the Zn/ZnSO 4 /MnO 2 rechargeable cell by Kim et al (Kim and Oh, 1998). Although the Zn/ZnSO 4 /MnO 2 rechargeable cell was not coined as ZIBs by Kim et al (Kim and Oh, 1998), the use of mildaqueous ZnSO 4 electrolyte for Zn/MnO 2 rechargeable cells could termed as ZIBs, as per the recent nomenclature.…”
Section: Overview Of the Evolutions Of Aqueous Rechargeable Batteriesmentioning
confidence: 99%
“…More MFBs can be constructed by leveraging the reversible transformations between various oxidation states of Mn, such as Mn 3+ /Mn 2+ , MnO 2 /Mn 2+ , and MnO − 4 /MnO 2− 4 pairs [23][24][25][26]. The redox reactions involving Mn 3+ /Mn 2+ typically occur in highly acidic environments (pH < 1), exhibiting a high potential (1.51 V vs SHE) and high solubility, which are advantageous for the development of MFBs with elevated energy density.…”
Section: Introductionmentioning
confidence: 99%